Nursing problems of patients in the postoperative period in terms of the International Classification for Nursing Practice - Grabowska, Hanna; Grabowski, Władysław (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Professional nursing care of patients performed in the postoperative period is aimed at ensuring patient safety, quick recovery, as well as the prevention of complications and pain relief. The aim of this work was an attempt to cross-map terms describing nursing problems of patients in the perioperative period with the interventions included in the ICNP catalogue.  The method of analysis and critique of literature was applied in this work. A review of selected publications showed complexity and diversity of the language used by the authors to describe nursing problems of patients in the postoperative period. Such a situation does not seem comfortable in view of implementing and popularizing electronic nursing documentation in Poland. The ICNP is a proposal to solve the problem - it is a simple, versatile, unambiguous and - most importantly - standardized tool.